Ferroptosis is involved in polymyxin B-induced acute kidney injury via activation of p53. (1st June 2023) - Li, Hongyu; Wang, Boying; Wu, Sheng; Dong, Shuying; Jiang, Guojun; Huang, Yingying; Tong, Xuhui; Yu, Meiling
Abstract: Polymyxin B (PMB) is one of the most effective drugs for the treatment of multi-resistant and pan-resistant gram-negative infections. However, it can induce acute kidney injury (AKI), the mechanism of which has not yet been fully elucidated. In this study, RNA sequencing and in vitro and in vivo experiments demonstrated that PMB induced AKI by promoting ferroptosis. Moreover, the metallothionein-1 (MT-1) level was significantly increased in the AKI group and clinical cases revealed that iron and MT-1 levels in urine were significantly higher in patients with AKI than in those without AKI. To explore the mechanism of PMB induced ferroptosis, we silenced p53 in human kidney-2 (HK2) cells according to RNA sequencing, which showed that p53 was obviously enhanced in the PMB treated group. While PMB significantly enhanced Fe 2+, lipid peroxidation, malondialdehyde (MDA), transferrin receptor protein 1 (TFR1), and arachidonate 12-lpoxygenase (ALOX12), decreased the survival rate, solute carrier family 7 member 11 (SLC7A11), glutathione peroxidase 4 (GPX4), and glutathione (GSH), downregulation of p53 reversed these effects, suggesting PMB induced ferroptosis by activating p53. Studies have shown p53 can promote ferroptosis by regulating the downstream factors SLC7A11 or TFR1. Further, we verified that silencing TFR1 expression as well as overexpression of SLC7A11 inhibited ferroptosis and significantly increased the survival rate of HK2 cells. Overall, PMB induces ferroptosis in renal tubular cells by activating p53 to reduce SLC7A11 expression and elevate TFR1, leading to AKI; MT-1 and iron levels in urine were significantly increased when PMB induced ferroptosis. Graphical abstract: PMB promoted ferroptosis by downregulating SLC7A11 and upregulating TFR1 expression  via  activation of p53. Image 1 Highlights: PMB induced ferroptosis in renal tubular cells. PMB induced acute kidney injury (AKI) by promoting ferroptosis. PMB induced ferroptosis by activating of p53. MT-1 was significantly increased when PMB induced ferroptosis.